Alkohol in obolenja srca - Letonja, Mitja (Medicinski razgledi, 2008)
Small amounts of alcohol consumption are associated with a decrease in the incidence of coronary artery disease and total mortality, whereas with higher alcohol consumption an increase in total and cardiovascular mortality is observed. Heavy drinking on weekends and during holidays leads to arrhythmias,particularly atrial fibrillation and conduction defects, which hasbeen termed the holiday heart syndrome . Long-term alcohol consumption is the leading cause of nonischemic, dilated cardiomyopathy. Alcoholic cardiomyophathy is a specific heart muscle disease with a known cause, which progresses because of continuous drinking, from the asymptomatic to the symptomatic stage with signs and symptoms of heart failure. Alcoholic cardiomyophathy is characterised by increased myocardial mass and dilatation of the ventricles. Changes in ventricular function depend on the stage, in that asymptomatic alcoholic cardiomyophathy is associated with diastolic dysfunction, whereas systolic dysfunction is a common finding in symptomatic patients. Alcohol abstinence, along with the use of specific heart failure pharmacotherapies, is critical in improving ventricular function and outcomes in these patients.
Keywords: Alcohol Drinking; Alkoholizem; Aritmija; Cardiomyopathy, Alcoholic; Diagnosis; Alkohol, pitje; Kardiomiopatija alkoholna; Alcoholism; Arrhythmia; pitje; srčne bolezni; kardiomiopatije